1988
DOI: 10.1016/s0022-5347(17)42494-3
|View full text |Cite
|
Sign up to set email alerts
|

M-Vac (Methotrexate, Vinblastine, Doxorubicin and Cisplatin) for Advanced Transitional Cell Carcinoma of the Urothelium

Abstract: Of 92 patients who received methotrexate, vinblastine, doxorubicin and cisplatin complete and partial remissions were observed in 69 +/- 10 per cent of 83 adequately treated measurable and evaluable patients with advanced stages (N+M0 and N0M+) transitional cell urothelial cancer. Complete remission was achieved in 37 +/- 10 per cent of the patients clinically, pathologically and after surgical resection of residual disease. With 17 of 31 complete responders (55 per cent) surviving for 26+ to 49+ months, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
181
0
17

Year Published

1994
1994
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 512 publications
(207 citation statements)
references
References 12 publications
9
181
0
17
Order By: Relevance
“…For this reason, adjuvant systemic chemotherapy should be investigated because good objective responses are observed in a palliative setting [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, adjuvant systemic chemotherapy should be investigated because good objective responses are observed in a palliative setting [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The combination regimen including methotrexate, vinblastine, doxorubicin and cisplatin (M-VAC) was devised at Memorial Sloan-Kettering in the mid 1980s (Sternberg et al, 1988) and improved overall survival to a median slightly in excess of 12 months and became the standard of care worldwide for advanced bladder cancer (Culine, 2002).…”
mentioning
confidence: 99%
“…1 Randomized trials subsequently demonstrated that when applied in the perioperative or metastatic settings, such treatment regimens prolonged patient survival. [2][3][4] However, despite this therapeutic advance, the vast majority of patients with metastatic urothelial cancer, and a large proportion of patients with muscle-invasive disease, will still succumb to their disease.…”
Section: Introductionmentioning
confidence: 99%